Conditionals in selection semantics - Cariani, Fabrizio (Proceedings of the Amsterdam Colloquium, 2019)
I explore the semantic and logical prospects for reconstructing Stalnakerian truth-conditions for conditionals on a theory on which these emerge from the separate contribution of selection modals (will and would) and a restrictor theory of if-clauses.